A method for preparing pre-lithiated silicon oxide negative electrode material

By using a prelithium method combined with a low concentration of prelithium solution and powder lithium source, amorphous or small crystal prelites of prelithium oxide carbon material is formed, which solves the problem of low efficiency of silicon oxide in the first cycle of lithium-ion batteries, and achieves a battery material with high first-term efficiency and high cycle performance.

CN116177553BActive Publication Date: 2025-04-25HEFEI GUOXUAN HIGH TECH POWER ENERGY

Patent Information

Application Number
CN202310082693.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2025-04-25
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

Silicon oxide is less efficient during the first cycle of lithium-ion batteries, resulting in the generation of irreversible capacity and affecting the use of electrode materials.

Method used

A prelithium method is adopted that combines a low-concentration prelithium solution and powder lithium source, and a process of combining atmosphere spray drying and solid phase sintering is formed with amorphous or small crystal grains.

Benefits of technology

It improves the first-time efficiency and cycling performance of the material, reduces the reduction of silicon oxide and the expansion of the material, and enhances the high energy density performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116177553B_ABST
    Figure CN116177553B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a pre-lithiated silicon oxide negative electrode material, comprising: S1, adding silicon oxide powder to a sodium alginate solution, stirring evenly, then adding a cross-linking agent solution and stirring to react, to obtain a hydrogel A; S2, heating the hydrogel A under an inert atmosphere to obtain a silicon-carbon composite material B; S3, mixing the silicon-carbon composite material B with a pre-lithium solution and stirring evenly, then spray drying in an inert atmosphere to obtain a pre-lithiated silicon-carbon composite material C; S4, mixing the pre-lithiated silicon-carbon composite material C with a lithium source, and calcining in an inert atmosphere. The pre-lithiated silicon oxide negative electrode material prepared by the present invention has a uniform internal structure and a high pre-lithium amount, has the characteristics of good cycle performance and high first efficiency, and the dense high-conductive carbon layer on the surface of the material can inhibit the expansion of the material during the charge and discharge cycle and reduce side reactions to improve the cycle performance of the material, thereby having the characteristics of both high first efficiency and high cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a method for preparing a pre-lithiated silicon monoxide negative electrode material. Background Art

[0002] Silicon oxide has attracted widespread attention as a lithium-ion negative electrode material due to its high capacity. At present, with the popularization of electric vehicles, the demand for high-energy-density lithium-ion batteries is increasing, and the use of silicon oxide negative electrode materials is also increasing. However, silicon oxide will form a large amount of lithium silicate phase during the first lithium insertion process of the cycle. These substances are irreversible in the subsequent cycle process, resulting in a low initial coulombic efficiency. Therefore, silicon oxide materials used as negative electrode materials for lithium-ion batteries generally need to be pre-magnesium or pre-lithium first to generate magnesium silicate or lithium silicate in advance, reduce the generation of irreversible capacity during the first lithium insertion process, and improve the first efficiency of the material. However, since the diffusion energy barrier of magnesium ions or lithium ions in the structurally stable solid silicon oxide is high, it needs to be completed under high magnesium or lithium concentrations and high temperatures. This process will destroy the stable structure of silicon oxide, resulting in a decrease in its cycle performance. Summary of the Invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a method for preparing a pre-lithiated silicon monoxide negative electrode material, and the prepared negative electrode material has the characteristics of high initial efficiency and high cycle performance.

[0004] The present invention provides a method for preparing a pre-lithiated silicon oxide negative electrode material, comprising the following steps:

[0005] S1. Add silicon dioxide powder to sodium alginate solution and stir evenly, then add crosslinker solution and stir to react to obtain hydrogel A;

[0006] S2. heating the hydrogel A to a certain temperature under an inert atmosphere to obtain a silicon-carbon composite material B;

[0007] S3, mixing the silicon-carbon composite material B with the pre-lithiation solution and stirring them uniformly to form a mixed slurry, and then spray-drying the mixed slurry in an inert atmosphere at a certain temperature to obtain a pre-lithiation silicon-carbon composite material C;

[0008] S4, mixing the pre-lithiated silicon-carbon composite material C with a lithium source, and calcining the mixture under an inert atmosphere to obtain the product.

[0009] Preferably, in S1, the mass ratio of silicon dioxide powder to sodium alginate is (5-10):1; in S1, the solid content of the sodium alginate solution is 0.1%-25%; in S1, the crosslinker solution is at least one of calcium chloride solution, calcium nitrate solution, and silver nitrate solution, and the concentration of the crosslinker solution is 0.01 mol / L-1 mol / L.

[0010] Preferably, the volume ratio of the cross-linking agent solution to the sodium alginate solution is 1:(3-5).

[0011] Preferably, in S1, the stirring speed is 100 r / min to 800 r / min.

[0012] Preferably, in S1, the silicon dioxide powder and the sodium alginate solution are mixed and stirred for 1 to 5 hours.

[0013] The sodium alginate solution is prepared by a conventional method, specifically, by adding sodium alginate into deionized water, stirring at a stirring speed of 100 to 800 r / min to form a uniform solution, thereby obtaining the sodium alginate solution.

[0014] Preferably, in S2, the temperature is heated to 400°C to 700°C.

[0015] Preferably, in S2, the heating rate is 3°C / min to 10°C / min.

[0016] Preferably, in S3, the solid content of the mixed slurry is 50% to 70%.

[0017] Preferably, in S3, the pre-lithium solution is obtained by dissolving lithium powder in a chelating agent solution, wherein the concentration of the chelating agent solution is 0.1 mol / L to 1 mol / L, and the mass ratio of the chelating agent to the lithium powder is (5 to 25):2.

[0018] Preferably, the chelating agent is at least one of naphthalene, biphenyl, 4-methylbiphenyl, 3-methylbiphenyl, dimethylnaphthalene, and 2-methylnaphthalene; the particle size of the lithium powder is 1 μm to 100 μm; the chelating agent solution is obtained by dissolving the chelating agent in a solvent, and the solvent is at least one of tetrahydrofuran, 4-methyltetrahydrofuran, and 2-methyltetrahydrofuran.

[0019] Preferably, in S3, the pre-lithium solution is obtained by adding lithium powder to a chelating agent solution and stirring until the lithium powder is completely dissolved, wherein the chelating agent solution is obtained by adding a chelating agent to a solvent and stirring uniformly.

[0020] Preferably, during the preparation of the pre-lithium solution and the chelating agent solution, the stirring speed is 100 r / min to 800 r / min.

[0021] Preferably, the preparation of the pre-lithium solution and the chelating agent solution is carried out at a constant temperature of 25°C to 45°C.

[0022] Preferably, in S3, the silicon-carbon composite material B is mixed with the pre-lithium solution and stirred for 1 hour to 10 hours.

[0023] Preferably, in S3, the stirring speed is 100 r / min to 800 r / min.

[0024] Preferably, in S3, the spray drying temperature is 200°C to 500°C.

[0025] Preferably, in S4, the mass ratio of the pre-lithiated silicon-carbon composite material C to the lithium source is (2.5-15):1; in S4, the lithium source is at least one of lithium hydride, lithium nitride, lithium orthosilicate, and lithium azide.

[0026] Preferably, in S4, the specific steps of calcining include: first heating to a first calcination temperature, keeping the temperature for 0.1h to 1h, then cooling to a second calcination temperature, keeping the temperature for 1.5h to 5h, wherein the first calcination temperature is 600℃ to 800℃, the second calcination temperature is 450℃ to 650, and the first calcination temperature - the second calcination temperature ≥ 100℃.

[0027] Preferably, in S4, the heating rate is 3°C / min to 10°C / min.

[0028] Preferably, in S4, the cooling rate is 1°C / min to 15°C / min.

[0029] A pre-lithiated silicon 2 oxide negative electrode material is prepared by the preparation method.

[0030] The present invention addresses the problem that the silicon oxide material of the negative electrode of a lithium-ion battery has low efficiency during the first cycle, which affects the use of the electrode material. Currently, the first efficiency is mainly improved by pre-magnesium or pre-lithium. However, the traditional process uses a single lithium source for pre-lithiation. A high pre-lithiation concentration easily causes silicon oxide reduction to form large silicon grains, which is not conducive to the material's cycle performance. Alternatively, a low pre-lithiation concentration results in a low first efficiency, which is not conducive to the preparation of high-energy-density batteries. The present invention combines two pre-lithiation methods: using a low-concentration pre-lithiation solution for pre-lithiation using atmosphere spray drying and using a powdered lithium source for solid-phase sintering. During the entire pre-lithiation process, the lithium concentration inside the silicon oxide particles is distributed in a gradient, which reduces the concentration of the lithium source and reduces the reduction of silicon oxide. Variable temperature solid-phase sintering is used to further reduce the material's grain size. Therefore, after pre-lithiation, the silicon oxide is amorphous or has small grains. The amorphous or small-grain silicon oxide carbon material prepared by this technology has a uniform internal structure and a high pre-lithiation amount, and has the characteristics of good cycle performance and high first efficiency. The dense, highly conductive carbon layer on the surface of the material can inhibit the expansion of the material during the charge-discharge cycle and reduce side reactions to improve the material's cycle performance.

[0031] The beneficial effects of the present invention are as follows:

[0032] The present invention adopts a gel cross-linking agent to cause sodium alginate to cross-link to form a hydrogel. After the high-viscosity hydrogel fixes silicon dioxide, it is carbonized in situ at low temperature to form a dense and uniform high-conductivity carbon layer. At this temperature, the silicon dioxide disproportionation temperature is not reached and no crystalline silicon will be produced. In addition, the present invention combines two pre-lithiation methods: using a low-concentration pre-lithium solution to perform atmosphere spray drying for pre-lithiation and using a lithium source for solid-phase sintering for pre-lithiation. Since the potential of the low-concentration pre-lithium solution is lower than that of the lithium source, the pre-lithium starting critical temperature of the pre-lithium solution is lower than that of the lithium source, and the diffusion speed is faster at the same temperature. Therefore, by first performing low-concentration pre-lithium spray drying for pre-lithiation and then performing solid-phase sintering for pre-lithiation, the pre-lithiation process is completed in the entire pre-lithiation process. During the lithiation process, the lithium concentration inside the silicon oxide particles is distributed in a gradient, which reduces the concentration of the lithium source and reduces the reduction of silicon oxide. At the same time, a dense and uniform high-conductive carbon layer is formed on the surface of silicon oxide, which further inhibits the reduction process of silicon oxide. Therefore, after pre-lithiation of this technology, the silicon oxide is amorphous or has small grains. In addition, the present invention also adopts a high-temperature followed by low-temperature pre-lithiation process. In the high-temperature stage, lithium can diffuse rapidly into the interior of the silicon-carbon composite material, reducing the lithium source concentration on the surface of the silicon-carbon composite material and reducing the reduction of silicon oxide. After a short period of rapid high-temperature diffusion, it is transformed into a low-temperature stage to provide diffusion energy, and the temperature is lower than the disproportionation temperature of silicon oxide, which reduces the nucleation and growth of silicon oxide.

[0033] The traditional process uses a single lithium source for pre-lithiation. When the pre-lithiation concentration is high, silicon oxide reduction is prone to form large silicon grains, which is not conducive to the material's cycle performance. Alternatively, when the pre-lithiation concentration is low, the first efficiency is low, which is not conducive to the preparation of high-energy density batteries. The present invention optimizes the preparation method of the pre-lithiated silicon oxide negative electrode material so that the prepared amorphous or small-grain silicon oxide carbon material has a uniform internal structure and a high pre-lithiation amount, and has the characteristics of good cycle performance and high first efficiency. The dense high-conductivity carbon layer on the surface of the material can inhibit the expansion of the material during the charge and discharge cycle and reduce side reactions to improve the material's cycle performance. Therefore, the pre-lithiated silicon oxide negative electrode material of the present invention can have the characteristics of high first efficiency and high cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the SEM image of the pre-lithiated silicon monoxide negative electrode material in Example 2.

[0035] Figure 2 This is the XRD pattern of the pre-lithiated silicon monoxide negative electrode material in Example 2. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is described in detail below through specific embodiments.

[0037] Example 1

[0038] Preparation of pre-lithiated silicon dioxide anode material:

[0039] S1. Add silicon dioxide powder to a sodium alginate solution with a solid content of 0.1%, stir at a stirring speed of 100 r / min to 800 r / min for 1 hour, then add a calcium chloride solution with a concentration of 0.01 mol / L, and stir at a stirring speed of 100 r / min to obtain hydrogel A; wherein the mass ratio of silicon dioxide powder to sodium alginate is 5:1, and the volume ratio of calcium chloride solution to sodium alginate solution is 1:4;

[0040] S2, heating the hydrogel A to 400° C. in an inert atmosphere furnace at a heating rate of 3° C. / min to obtain a silicon-carbon composite material B;

[0041] S3, after mixing the silicon-carbon composite material B with the pre-lithium solution, stirring at a stirring speed of 100r / min for 1h to form a mixed slurry with a solid content of 60%, and then spray-drying at 200°C in an inert atmosphere to obtain a pre-lithiated silicon-carbon composite material C, wherein the preparation method of the pre-lithium solution is as follows: at a constant temperature of 25°C, naphthalene is first added to tetrahydrofuran and stirred at a stirring speed of 300r / min to obtain a 0.1mol / L chelating agent solution, and then lithium powder with a particle size of 1μm (wherein the mass ratio of naphthalene to lithium powder is 25:2) is added to the chelating agent solution, and stirred at a stirring speed of 100r / min until completely dissolved to obtain a pre-lithium solution;

[0042] S4. After uniformly mixing the pre-lithiated silicon-carbon composite material C and lithium hydride in a mass ratio of 15:1, heat to 600°C at a heating rate of 3°C / min / min in an inert atmosphere furnace, keep warm and calcine for 0.1h, then cool to 450°C at a cooling rate of 1°C / min, keep warm and calcine for 1.5h to obtain the product.

[0043] The obtained pre-lithiated silicon oxide negative electrode material and metallic lithium were used to form a half-cell for electrochemical performance testing. The test rate was 0.1C (first cycle) + 0.5C (cycle), and the charge and discharge voltage was 0.005-0.8V. The results showed that the discharge capacity of the negative electrode sheet can reach 1250mAh / g, with an initial efficiency of 91.6%. After 50 cycles, it can still maintain 80.1% of the capacity.

[0044] Example 2

[0045] Preparation of pre-lithiated silicon dioxide anode material:

[0046] S1. Adding silicon dioxide powder to a sodium alginate solution having a solid content of 1%, stirring at a stirring speed of 200 r / min for 1.5 h, then adding a calcium chloride solution having a concentration of 0.5 mol / L, stirring at a stirring speed of 150 r / min to react, to obtain hydrogel A; wherein the mass ratio of silicon dioxide powder to sodium alginate is 6:1, and the volume ratio of calcium chloride solution to sodium alginate solution is 1:4;

[0047] S2. Heating the hydrogel A to 500° C. at a heating rate of 4° C. / min in an inert atmosphere furnace to obtain a silicon-carbon composite material B;

[0048] S3. After mixing the silicon-carbon composite material B with the pre-lithium solution, stirring at a stirring speed of 250 r / min for 2 hours to form a mixed slurry with a solid content of 60%, and then spray-drying at 300° C. in an inert atmosphere to obtain a pre-lithiated silicon-carbon composite material C, wherein the preparation method of the pre-lithium solution is as follows: at a constant temperature of 35° C., first, a mixture of biphenyl and 4-methylbiphenyl in a mass ratio of 1:1 is added to 4-methyltetrahydrofuran and stirred at a stirring speed of 400 r / min to obtain a 0.2 mol / L chelating agent solution, and then lithium powder with a particle size of 5 μm (wherein the mass ratio of the chelating agent to the lithium powder is 6:1) is added to the chelating agent solution, and stirred at a stirring speed of 150 r / min until completely dissolved to obtain a pre-lithium solution;

[0049] S4. After uniformly mixing the pre-lithiated silicon-carbon composite material C and lithium nitride in a mass ratio of 8:1, heat to 620°C at a heating rate of 5°C / min in an inert atmosphere furnace, keep warm and calcine for 0.5h, then cool to 480°C at a cooling rate of 5°C / min, keep warm and calcine for 2h to obtain the product.

[0050] The obtained pre-lithiated silicon oxide anode material and metallic lithium were used to form a half-cell for electrochemical performance testing. The test rate was 0.1C (first cycle) + 0.5C (cycle), and the charge and discharge voltage was 0.005-0.8V. The results showed that the discharge capacity of the negative electrode sheet can reach 1237mAh / g, with an initial efficiency of 89.6%. After 50 cycles, it can still maintain 81.1% of the capacity.

[0051] Figure 1 This is the SEM image of the prepared pre-lithiated silicon dioxide negative electrode material. It can be seen that the surface of the silicon-carbon material is flat and evenly covered with a carbon layer. Figure 2 This is the XRD diagram of the prepared pre-lithiated silicon dioxide negative electrode material. It can be seen that the silicon-carbon material has small silicon grains and uniform pre-lithiation, with only Li2SiO3 lithium silicate phase and uniform material structure.

[0052] Example 3

[0053] Preparation of pre-lithiated silicon dioxide anode material:

[0054] S1. Adding silicon oxide powder to a sodium alginate solution having a solid content of 5%, stirring at a stirring speed of 300 r / min for 2 h, then adding a calcium nitrate solution having a concentration of 0.6 mol / L, stirring at a stirring speed of 450 r / min to react, to obtain hydrogel A; wherein the mass ratio of silicon oxide powder to sodium alginate is 7:1, and the volume ratio of calcium nitrate solution to sodium alginate solution is 1:4;

[0055] S2. Heating the hydrogel A to 510° C. in an inert atmosphere furnace at a heating rate of 6° C. / min to obtain a silicon-carbon composite material B;

[0056] S3. After mixing the silicon-carbon composite material B with the pre-lithium solution, stirring at a stirring speed of 400 r / min for 3 hours to form a mixed slurry with a solid content of 60%, and then spray-drying at 350° C. in an inert atmosphere to obtain a pre-lithiated silicon-carbon composite material C, wherein the preparation method of the pre-lithium solution is as follows: at a constant temperature of 36° C., first, adding a mixture of 3-methylbiphenyl and dimethylnaphthalene in a mass ratio of 1:2 to 2-methyltetrahydrofuran and stirring at a stirring speed of 400 r / min to obtain a 0.6 mol / L chelating agent solution, and then adding lithium powder with a particle size of 50 μm to the chelating agent solution (wherein the mass ratio of the chelating agent to the lithium powder is 13:2) and stirring at a stirring speed of 400 r / min until completely dissolved to obtain a pre-lithium solution;

[0057] S4. After uniformly mixing the pre-lithiated silicon-carbon composite material C and lithium orthosilicate in a mass ratio of 10:1, heat them to 650°C at a heating rate of 3°C / min in an inert atmosphere furnace, keep them warm and calcine for 0.6h, then cool them to 500°C at a cooling rate of 8°C / min, keep them warm and calcine for 3h to obtain the product.

[0058] The obtained pre-lithiated silicon oxide anode material and metallic lithium were used to form a half-cell for electrochemical performance testing. The test rate was 0.1C (first cycle) + 0.5C (cycle), and the charge and discharge voltage was 0.005-0.8V. The results showed that the discharge capacity of the negative electrode sheet can reach 1230mAh / g, with an initial efficiency of 93.0%. After 50 cycles, it can still maintain 83.1% of the capacity.

[0059] Example 4

[0060] Preparation of pre-lithiated silicon dioxide anode material:

[0061] S1. Adding silicon oxide powder to a sodium alginate solution having a solid content of 15%, stirring at a stirring speed of 800 r / min for 3 h, then adding a calcium nitrate solution having a concentration of 0.8 mol / L, and stirring at a stirring speed of 600 r / min to react to obtain hydrogel A; wherein the mass ratio of silicon oxide powder to sodium alginate is 8:1, and the volume ratio of calcium nitrate solution to sodium alginate solution is 1:4;

[0062] S2. Heating the hydrogel A to 510° C. in an inert atmosphere furnace at a heating rate of 6° C. / min to obtain a silicon-carbon composite material B;

[0063] S3. After mixing the silicon-carbon composite material B with the pre-lithium solution, stirring at a stirring speed of 400 r / min for 5 hours to form a mixed slurry with a solid content of 50%, and then spray-drying at 400° C. in an inert atmosphere to obtain a pre-lithiated silicon-carbon composite material C, wherein the preparation method of the pre-lithium solution is as follows: at a constant temperature of 40° C., first adding dimethylnaphthalene to 2-methyltetrahydrofuran and stirring at a stirring speed of 400 r / min to obtain a 0.8 mol / L chelating agent solution, and then adding lithium powder with a particle size of 60 μm (wherein the mass ratio of dimethylnaphthalene to lithium powder is 11:2) to the chelating agent solution, stirring at a stirring speed of 400 r / min until completely dissolved to obtain a pre-lithium solution;

[0064] S4. After uniformly mixing the pre-lithiated silicon-carbon composite material C and lithium orthosilicate in a mass ratio of 6:1, heat them to 700°C in an inert atmosphere furnace at a heating rate of 5°C / min, keep them warm and calcine for 0.8h, then cool them to 600°C at a cooling rate of 8°C / min, keep them warm and calcine for 4h to obtain the product.

[0065] The obtained high-initial efficiency silicon monoxide and metallic lithium were combined into a half-cell for electrochemical performance testing at a test rate of 0.1C (initial) + 0.5C (cycle), with a charge and discharge voltage of 0.005-0.8V. The results showed that the discharge specific capacity of the negative electrode can reach 1220mAh / g, with an initial efficiency of 92.2%. After 50 cycles, it can still maintain 80.1% of the capacity.

[0066] Example 5

[0067] Preparation of pre-lithiated silicon dioxide anode material:

[0068] S1. Adding silicon oxide powder to a sodium alginate solution having a solid content of 25%, stirring at a stirring speed of 800 r / min for 5 h, then adding a silver nitrate solution having a concentration of 1 mol / L, stirring at a stirring speed of 800 r / min to react, to obtain hydrogel A; wherein the mass ratio of silicon oxide powder to sodium alginate is 10:1, and the volume ratio of silver nitrate solution to sodium alginate solution is 1:4;

[0069] S2. Heating the hydrogel A to 510° C. at a heating rate of 10° C. / min in an inert atmosphere furnace to obtain a silicon-carbon composite material B;

[0070] S3. After mixing the silicon-carbon composite material B with the pre-lithium solution, stirring at a stirring speed of 400 r / min for 10 hours to form a mixed slurry with a solid content of 70%, and then spray-drying at 500° C. in an inert atmosphere to obtain a pre-lithiated silicon-carbon composite material C, wherein the preparation method of the pre-lithium solution is as follows: at a constant temperature of 45° C., first adding 2-methylnaphthalene to 2-methyltetrahydrofuran and stirring at a stirring speed of 400 r / min to obtain a 0.8 mol / L chelating agent solution, and then adding lithium powder with a particle size of 100 μm (wherein the mass ratio of 2-methylnaphthalene to lithium powder is 5:2) to the chelating agent solution, and stirring at a stirring speed of 400 r / min until completely dissolved to obtain a pre-lithium solution;

[0071] S4. After uniformly mixing the pre-lithiated silicon-carbon composite material C and lithium hydride in a mass ratio of 5:2, heat them to 800°C in an inert atmosphere furnace at a heating rate of 10°C / min, keep them warm and calcine for 1 hour, then cool them to 650°C at a cooling rate of 15°C / min, keep them warm and calcine for 5 hours to obtain the product.

[0072] The obtained pre-lithiated silicon oxide anode material and metallic lithium were used to form a half-cell for electrochemical performance testing. The test rate was 0.1C (first cycle) + 0.5C (cycle), and the charge and discharge voltage was 0.005-0.8V. The results showed that the discharge capacity of the negative electrode sheet can reach 1253mAh / g, with an initial efficiency of 93.0%. After 50 cycles, it can still maintain 81.1% of the capacity.

[0073] Comparative Example 1

[0074] Comparative Example 1 is a conventional method for preparing pre-lithiated silicon dioxide, which is as follows:

[0075] The silicon oxide was placed in a CVD furnace and argon was passed through to replace the air. Argon was continuously passed through at a flow rate of 300 ml / min, and the temperature was raised to 900 ° C at 3 ° C / min. Acetylene was passed through at a flow rate of 300 ml / min and calcined for 1.5 hours. The material was then taken out after cooling, and the material was mixed with lithium powder at a mass ratio of 10:1. The material was placed in an atmosphere box furnace and calcined for 5 hours under an argon atmosphere to obtain a pre-lithiated silicon-carbon material. The obtained pre-lithiated silicon oxide negative electrode material and metallic lithium were used to form a half-cell for electrochemical performance testing. The test rate was 0.1C (first) + 0.5C (cycle), and the charge and discharge voltage was 0.005~0.8V. The results showed that the discharge capacity of the negative electrode sheet can reach 1200mAh / g, the first efficiency is 92.0%, and after 50 cycles, the capacity can still be maintained at 51.1%.

[0076] It can be seen from the performance results of the embodiment that the present technical solution is achieved by: using a cross-linking agent solution to cause sodium alginate to cross-link to form a hydrogel, and after the high-viscosity hydrogel fixes silicon oxide, it is subjected to low-temperature in-situ carbonization to form a dense and uniform high-conductivity carbon layer. At this temperature, the silicon oxide disproportionation temperature is not reached and no crystalline silicon will be produced. In addition, the present patent combines two pre-lithiation methods: pre-lithiation by atmosphere spray drying with a low-concentration pre-lithiation solution and solid-phase sintering with a lithium source. The potential of the low-concentration pre-lithiation solution is lower than that of the lithium source. Therefore, compared with the lithium source, the pre-lithiation starting critical temperature of the pre-lithiation solution is lower and the diffusion rate is faster at the same temperature. Therefore, in the entire pre-lithiation process of first low-temperature spray drying pre-lithiation and then solid-phase sintering pre-lithiation, the lithium concentration inside the silicon oxide particles is gradiently distributed, which reduces the concentration of the lithium source and reduces the reduction of silicon oxide. At the same time, the dense and uniform high-conductivity carbon layer formed on the surface of silicon oxide further inhibits the reduction process of silicon oxide. Therefore, after pre-lithiation by this method, silicon oxide is amorphous or small grains. In addition, in the solid-phase sintering pre-lithiation process, a variable temperature pre-lithiation process of first high temperature and then low temperature is adopted. In the high temperature stage, lithium can quickly diffuse into the interior of the silicon-carbon composite material, reducing the lithium source concentration on the surface of the silicon-carbon composite material. After a short period of high-temperature rapid diffusion, it is transformed into a low temperature stage to provide diffusion energy, and the temperature is lower than the disproportionation temperature of silicon oxide, reducing the nucleation and growth of silicon oxide. Compared with the traditional process of using a single lithium source for pre-lithiation, high pre-lithiation concentration is prone to silicon oxide reduction to form large silicon grains, which is not conducive to the material cycle performance, or low pre-lithiation concentration leads to low first efficiency, which is not conducive to the preparation of high energy density batteries, the amorphous or small-grain silicon oxide carbon material prepared by the technology of the present invention has a uniform internal structure and a high pre-lithiation amount, and has the characteristics of good cycle performance and high first efficiency. In addition, the dense high-conductive carbon layer on the surface of the material can inhibit the expansion of the material during the charge and discharge cycle and reduce side reactions to improve the cycle performance of the material.

[0077] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. A method for preparing a pre-lithiated silicon oxide negative electrode material, characterized in that: The following steps are involved: S1, adding silicon dioxide powder to sodium alginate solution, stirring evenly, and then adding crosslinking agent solution to stir and react, to obtain hydrogel A; the crosslinking agent solution is at least one of calcium chloride solution, calcium nitrate solution, and silver nitrate solution; S2, heating the hydrogel A to 400° C. to 700° C. under an inert atmosphere to obtain a silicon-carbon composite material B; S3, mixing the silicon-carbon composite material B with the pre-lithium solution and stirring them evenly to form a mixed slurry, and then spray drying them in an inert atmosphere at a certain temperature to obtain a pre-lithiated silicon-carbon composite material C; the pre-lithium solution is obtained by dissolving lithium powder in a chelating agent solution, wherein the concentration of the chelating agent solution is 0.1 mol / L to 1 mol / L, and the mass ratio of the chelating agent to the lithium powder is (5 to 25):2; the chelating agent is at least one of naphthalene, biphenyl, 4-methylbiphenyl, 3-methylbiphenyl, dimethylnaphthalene, and 2-methylnaphthalene; S4. After mixing the pre-lithiation silicon-carbon composite material C with a lithium source, calcining them under an inert atmosphere to obtain; the lithium source is at least one of lithium hydride, lithium nitride, lithium orthosilicate, and lithium azide; the specific steps of calcination include: first heating to a first calcination temperature, keeping the temperature for 0.1h to 1h, then cooling to a second calcination temperature, keeping the temperature for 1.5h to 5h, wherein the first calcination temperature is 600℃ to 800℃, the second calcination temperature is 450℃ to 650℃, and the first calcination temperature - the second calcination temperature ≥100℃.

2. The method for preparing the pre-lithiated silicon oxide negative electrode material according to claim 1, characterized in that: In S1, the mass ratio of silicon dioxide powder to sodium alginate is (5-10):1; in S1, the solid content of the sodium alginate solution is 0.1%-25%; in S1, the concentration of the crosslinking agent solution is 0.01 mol / L-1 mol / L.

3. The method for preparing the pre-lithiated silicon oxide negative electrode material according to claim 1, characterized in that: In S3, the solid content of the mixed slurry is 50% to 70%.

4. The method for preparing the pre-lithiated silicon oxide negative electrode material according to claim 1, characterized in that: The particle size of the lithium powder is 1 μm to 100 μm; the chelating agent solution is obtained by dissolving the chelating agent in a solvent, and the solvent is at least one of tetrahydrofuran, 4-methyltetrahydrofuran and 2-methyltetrahydrofuran.

5. The method for preparing the pre-lithiated silicon oxide negative electrode material according to claim 1, characterized in that: In S3, the spray drying temperature is 200°C to 500°C.

6. The method for preparing the pre-lithiated silicon oxide negative electrode material according to claim 1, characterized in that: In S4, the mass ratio of the pre-lithiation silicon-carbon composite material C to the lithium source is (2.5-15):

1.

7. A pre-lithiated silicon oxide negative electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Modified silicon-based negative electrode material, preparation method and application thereof

    CN105932224A

  • High-first-effect silicon monoxide negative electrode and preparation method thereof

    CN114275785A

  • Silicon monoxide / carbon composite material, preparation method thereof and lithium ion battery

    CN114804117A

Cited By

  • Nitrogen-doped carbon silicon / reduced graphene oxide composite negative electrode material and preparation method thereof

    CN122177776A